Targeted delivery of BACE1 siRNA for synergistic treatment of Alzheimer's disease - Zhaohan Li; Jun Yang; Jianan Li; Shuxuan Zhao; Shaoping Jiang; Weimin Liu; Xinjian Li; Simeng Zhang; Haiyan Du; Junjun Ni; Yuanyu Huang; Hong Qing; et al. (Translational Neurodegeneration)
Abstract Background The deposition of toxic aggregated amyloid-β (Aβ), resulting from continuous cleavage of amyloid precursor protein (APP) by β-site APP cleaving enzyme 1 (BACE1) and γ-secretase, is a key pathogenic event in Alzheimer's disease (AD). Small interfering RNAs (siRNA) have shown great potential for disease treatment by specifically silencing target genes. However, the poor brain delivery efficiency of siRNAs limits their therapeutic efficacy against AD. Methods We designed a simplified and effective BACE1 siRNA (siBACE1) delivery system, namely, dendritic polyamidoamine modified with the neurotropic virus-derived peptide RVG29 and polyethylene glycol (PPR@siBACE1). Results PPR@siBACE1 crossed the blood–brain barrier efficiently and entered brain parenchyma in large amount, with subsequent neurotropism and potential microglia-targeting ability. Both in vitro and in vivo studies validated the effective brain delivery of siBACE1 and strong BACE1 silencing efficiency. Treatment of AD mice with PPR@siBACE1 inhibited the production of Aβ, potentiated Aβ phagocytosis by microglia, improved the memory deficits and reduced neuroinflammatory response in AD mice. Conclusions This study provides a reliable delivery platform for gene therapies for AD.